Techno-economic analysis of hybrid photovoltaic and stirling engine generator for offshore oil and gas platform - Superman Misdi; Jaka Windarta; Mohamad Said Kartono Tony Suryo Utomo (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2026)
The increasing demand for sustainable offshore oil and gas operations has driven the exploration of efficient and environmentally friendly hybrid energy systems. Conventional fossil fuel-based systems' consumption significantly contributes to greenhouse gas emissions and creates a need for innovative solutions that address environmental challenges while maintaining operational effectiveness. This study aims to analyse and evaluate a hybrid energy system that combines Stirling Engine Generator (SEG) technology and Photovoltaic (PV) panels, with the primary goal of enhancing energy efficiency, reducing carbon emissions, and improving the sustainability of offshore oil and gas operations. A comprehensive approach, integrating manual calculations and PVsyst software simulations, was used to analyse the performance of the Stirling and PV hybrid system. The research findings indicate that the hybrid system significantly improves energy efficiency and carbon emissions reduction compared to a fossil fuel-based system, with SEG utilizing heat from natural gas combustion and PV panels capturing solar energy, creating a synergistic effect with better overall performance and a lower environmental impact. Economically, the hybrid system minimizes fuel dependency and maintenance costs, benefiting from PV panels’ lower operational expenses compared to a fuel-based system. This combination not only aids emission reduction efforts but also presents a cost-effective solution over time, with the system’s ability to harness renewable energy and support compliance with emission reduction regulations. In conclusion, integrating SEG and PV technologies in a hybrid system offers a practical pathway to achieving emission reduction targets and maintaining operational efficiency, marking a step toward environmentally and economically sustainable practices in offshore oil and gas operations.